Anti-Inflammatory Activity of Basella Alba Linn. in Albino Rats - Krishna Chaitanya.B (Journal of Applied Pharmaceutical Science)
The traditional medicinal plant Basella alba belongs to Basellaceae. Earlier folklore claims reports that the plant is used in inflammatory conditions. Inflammation is the complex biological response of vascular tissues to harmful stimuli, such as pathogens, damaged cells, or irritants. The present work was focused to evaluate anti inflammatory activity by cotton pellet granuloma method. The Basella alba leaves were subjected to cold maceration process by using solvent, 50% ethanol for 48hrs. The extract was obtained by filtration. The filtrate was freeze dried to get the powder product. The extract was mixed with 2% gum acacia to prepare suspension for oral dose. Sub acute inflammation was produced by cotton pellet granuloma. Sterile cotton (50+1mg) soaked in 0.2 ml of distilled water containing penicillin (0.1mg) and streptomycin (0.13mg) was implanted subcutaneously by incision on the back under ether anesthesia. Drugs were orally administered for 6days, the animal was sacrificed on seventh day and granuloma was dissected out, dried in oven for 24 hrs and weighed. The percentage inhibition was determined. To test the anti inflammatory activity phenyl butazone was taken as standard. Effect of different treatment (control, phenyl butazone, BLE-1, BLE-2) in sub acute inflammatory models in rats was studied and percentage inhibition of inflammation of standard and drug extract was compared in the present study. As the availability, cost and side effect of synthetic drugs impact on health as well as economy, mankind should go for natural treatment should go for natural treatment prior to synthetic drug.
Keywords: Pellet granuloma, BLE-1, BLE-2, phenyl butazone, freeze drying.